2017
DOI: 10.1016/j.alit.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody profiles and their association with blood eosinophils in asthma and COPD

Abstract: It is possible that asthma tends to involve autoimmunity associated with antinuclear antibody more frequently than COPD because asthma is the more robust factor for antinuclear antibody positivity. Antinuclear antibody and rheumatoid factor are associated with eosinophilic responses, but they do not work as biomarkers for disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 28 The latter study, however, showed that ANAs were predictors of asthma exacerbations, mortality and decrease in lung function. In contrast, the study by Tamai and co-workers 27 reported no correlation with clinical indices of severe asthma in patients who showed ANAs at clinically relevant titers of 1:160.…”
Section: Autoimmune Phenomena In Asthma: Evidence From Immunological mentioning
confidence: 84%
See 1 more Smart Citation
“… 28 The latter study, however, showed that ANAs were predictors of asthma exacerbations, mortality and decrease in lung function. In contrast, the study by Tamai and co-workers 27 reported no correlation with clinical indices of severe asthma in patients who showed ANAs at clinically relevant titers of 1:160.…”
Section: Autoimmune Phenomena In Asthma: Evidence From Immunological mentioning
confidence: 84%
“…However, another study reported that clinically significant high ANA titers ≥1:160 was detected in 10% of patients with asthma but there was no significant association between ANA positivity and clinical indices of asthma severity. 27 There were conflicting reports of clinical signs of ANAs between these studies. While signs of autoimmune manifestations such as rheumatic symptoms, cold sensitivity and Raynaud's phenomenon were reported in patients with low titer 1:40, 26 while the study with patients with higher ANA titers (>1:100) reported otherwise.…”
Section: Autoimmune Phenomena In Asthma: Evidence From Immunological mentioning
confidence: 99%
“…Autoantibodies (Abs) are a hallmark of autoimmunity. Increased levels of Abs have been detected in most autoimmune disorders 7. In asthmatic patients, especially non-allergic asthmatics, several elevated serum Abs (Se-Abs) against bronchial tissue antigens and nuclear antigens have been detected, which further provides evidence that the cause of asthma may be related to autoimmune dysregulation 8910111213141516…”
Section: Introductionmentioning
confidence: 93%
“…We conducted a prospective study to measure 10 types of Abs in matched Sp and Se samples and further compared and analyzed their associations with clinical characteristics. Our selected Abs—Ab against proteinase-3 (anti-PR3), Ab against La/Sjögren syndrome type B antigen (anti-SSB), Ab against Ro/Sjögren syndrome type A antigen (anti-SSA), Ab against Smith antigen (anti-Sm), Ab against ribosomal phosphoprotein P0 (anti-P0), Ab against DNA topoisomerase (anti-Scl-70), Ab against histidyl-tRNA synthetase (anti-Jo1), Ab against U1 small nuclear ribonucleoprotein (anti-U1-SnRNP), Ab against myeloperoxidase (anti-MPO) and Ab against thyroid peroxidase (anti-TPO)—have been examined in previous research aiming to explore the relationship between asthma and autoimmune disease716 or commonly present in autoimmune diseases 19…”
Section: Introductionmentioning
confidence: 99%
“…The role of autoimmunity in chronic airway diseases such as asthma and COPD has obtained attention in recent years (9)(10)(11)(12). Airway inflammation in COPD is heterogeneous in nature and pattern.…”
Section: Introductionmentioning
confidence: 99%